Clinical and patient-reported outcomes and neurofilament response during tofersen treatment in SOD1-related ALS: a multicenter observational study over 18 months - Meyer, Thomas; Schumann, Peggy; Weydt, Patrick; Petri, Susanne; Weishaupt, Jochen H.; Weyen, Ute; Koch, Jan C.; Günther, René; Regensburger, Martin; Boentert, Matthias; Wiesenfarth, Maximilian; Koc, Yasemin; et al. (Muscle & nerve, 2024)
Introduction/Aims In amyotrophic lateral sclerosis (ALS) caused by SOD1 mutations (SOD1-ALS), tofersen received accelerated approval in the United States and is available via expanded access programs (EAP) outside the United States. This multicenter study investigates clinical and patient-reported outcomes (PRO) and serum neurofilament light chain (sNfL) during tofersen treatment in an EAP in Germany. Methods Sixteen SOD1-ALS patients receiving tofersen for at least 6 months were analyzed. The ALS progression rate (ALS-PR), as measured by the monthly change of the ALS functional rating scale—revised (ALSFRS-R), slow vital capacity (SVC), and sNfL were investigated. PRO included the Measure Yourself Medical Outcome Profile (MYMOP2), Treatment Satisfaction Questionnaire for Medication (TSQM-9), and Net Promoter Score (NPS). Results Mean tofersen treatment was 11 months (6-18 months). ALS-PR showed a mean change of −0.2 (range 0 to −1.1) and relative reduction by 25%. Seven patients demonstrated increased ALSFRS-R. SVC was stable (mean 88%, range −15% to +28%). sNfL decreased in all patients except one heterozygous D91A-SOD1 mutation carrier (mean change of sNfL −58%, range −91 to +27%, p < .01). MYMOP2 indicated improved symptom severity (n = 10) or yet perception of partial response (n = 6). TSQM-9 showed high global treatment satisfaction (mean 83, SD 16) although the convenience of drug administration was modest (mean 50, SD 27). NPS revealed a very high recommendation rate for tofersen (NPS +80). Discussion Data from this EAP supported the clinical and sNfL response to tofersen in SOD1-ALS. PRO suggested a favorable patient perception of tofersen treatment in clinical practice.
Erstmals veröffentlicht: 20. Juni 2024
Gesehen am 26.11.2024